Analisis Miskonsepsi Pada Materi Larutan Elektrolit Dan Non-Elektrolit Siswa Kelas X Di SMA Kristen Eben Haezer Ibu Halmahera Barat - Noverlin Gootoro; Jeanne M. Tuerah (Chemistry Department, Universitas Negeri Manado, 2022)
The purpose of this study was to find out how much misconception analysis is on the material of electrolyte and non-electrolyte solutions for class X students at SMA Kristen Eben Haezer, West Halmahera, the research method used in this study is a qualitative descriptive approach. The results of this study indicate that there are two stages of testing, namely: (1. Validity test is Valid, meaning that the ability of the item to support the construct in the instrument. To test the validity of the construct can be done by asking from an expert (expert judgment). After construct testing is completed, it is continued with After being tabulated, the validity test is carried out with the help of Excel 2013. (2. Reliability Test is the reliability of the instrument is the level of stability of the instrument when used when and by anyone so that it will tend to produce the same or almost the same data as before. This means that the instrument used is the same as before. that will be used in this study will give the same results even though the reliability test is repeated using the Rash Model analysis with the help of Winsteps.